Kajian Normatif Pertanggungjawaban Perusahaan atas Pelaksanaan dan Pelaporan CSR Berdasarkan PP Nomor 47 Tahun 2012 - Endang Retno Suryowati; I Gusti Ayu Ketut Rachmi Handayani (Prosiding Seminar Nasional Ilmu Hukum, 2025)
TJSL/CSR in Indonesia is regulated as a legal obligation (mandatory) for companies engaged in the natural resources sector. Its success depends on the principle of accountability, which requires transparency and responsibility. This normative-juridical study evaluates the application of accountability principles in the mining sector. Normatively, PP 47/2012 requires CSR to be listed as an expense and focused on sustainable development (PPM). However, this regulation is not robust because it does not set a minimum fund allocation or clear program boundaries, allowing for multiple interpretations. Empirically (Sekotong case study), accountability is implemented in a formalistic manner, consisting only of one-way administrative reports without meaningful participation from the affected communities. A significant weakness is apparent when dealing with the increase in illegal gold mining (PETI) in legal concession areas. This situation results in a vacuum of responsibility. Companies can claim environmental damage caused by PETI, so that responsibility does not successfully ensnare corporate negligence in prevention efforts. The CSR accountability structure in Indonesia is weak because it only emphasizes activities that are carried out, not negligence that is overlooked. Regulatory reform is needed so that accountability includes passive responsibility to ensure that TJSL functions as a significant instrument of sustainable development.